SIMILARITY MELODY ANALYZING USING THE EARTH MOVER'S DISTANCE - Kusuma, Wahyu (Universitas Gunadarma, 2009)
In music information retrival system, queries are generally in the text form information, such as song title,singer name, song or composer. Beside that queries can also be a music signal or signal vocal (vocal melody)like singing, humming of a part song. This objective of the research is to analyze the vocal melody as similaritiesvocal melody for query data with melody as the target data. Similarities method used is the Earth MovingDistance (EMD). To analyze the similarities accuration, so in this research needs to be done melody processrepresentation through segmentation method with detection onset. Melody representation generated in theformat of onset time, pitch intervals, and time ratio of interval onset. In onset detection, signal goes throughfiltering process, rectification, the formation of the signal contours, gradient detection, and the selection signalabove the threshold value. Onset positions are used for signal segmentation, so that each segment contains onlyone note. Furthermore, each segment goes through the pitch exploration by frequency analysis with Fouriertransformation and pitch estimation with a fundamental frequency distribution approach.Based on results of distance value test used the EMD distance values, can be determined rank value and themean reciprocal rank (MRR). Tests conducted on 30 query data (sing and hum) with 30 data document (piano)so obtained MRR values equal to 0479. In the performance calculation in rank-6 performance on theperformance obtained equal to 93.3%. Test results show the accuracy similarities and retrival systemperformance using EMD was good.Keywords: extraction, representationf melody, similarities, music information retrivalCategories: H.5.Information Interface and Presentation | H.5.5.Sound and Music Computing | Signal Analysis,Synthesis, and Processing